Perbandingan Hasil Identifikasi Tricophyton Sp. dengan metode Mikroskop dan Kultur - Amelia Putri Az Zahra; Azlinatul Lulu Kharolaini; Elsa Oktavia Ramadhani; Pramai Sheila Eka Khoireina; Pramesti Listanto; Juwita Ramadhani Octavianingrum; Liss Dyah Dewi Arini (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
Trichophyton is a genus of dermatophytes that most frequently causes superficial infections in humans, particularly tinea capitis, tinea corporis, tinea pedis, and onychomycosis. Accurate identification of Trichophyton species is crucial for determining appropriate antifungal therapy. Routine dermatophyte identification has relied on macroscopic and microscopic morphology, but this approach is considered time-consuming. This article compares the results of Trichophyton fungal observations using two main approaches: direct microscopic observation using KOH solution and culture methods on selective media such as Sabouraud Dextrose Agar (SDA). Phenotype-based identification is performed through colony characteristics in culture and microscopic examination in lactophenol cotton blue preparations. From KOH and culture examinations of clinical samples, the positivity rate by KOH is generally higher than that by culture, although culture remains the reference standard for dermatophyte species identification. From KOH and culture examinations of clinical samples, the positivity rate by KOH is generally higher than that by culture, although culture remains the reference standard for dermatophyte species identification. A comprehensive understanding of these two methods is expected to improve the accuracy of clinical mycological diagnoses and support more targeted therapeutic management.